Viability of Islamic science: some insights from 19th century India - Habib, S. Irfan (2004)
Science flowered in Islam during the liberal Muslim Abbasid and later Ottoman kings. This was possible because the Abbasids welcomed scientists and translators from other cultures who willingly became sincere participants in the project called Islamic civilisation. The 19th century interlocutors, a few of whom are discussed in this paper, were aware of the cross-civilisational character of science in Islamic civilisation and modern science for them was a culmination of the perpetually shifting centres of science in history. This plurality of vision and cross-cultural perspective is much in contrast to what is being propounded today in the name of Islamic science. - Reproduced.
Keywords: Islamic culture